The perception of UPM’S students in outdoor recreation camp - Baharudin, Nur Syakirah (2019)
The motivation behind this investigation is to evaluate the student' observation on going to outdoor recreation camp then the impact of camp in student’s expectation. The growth of outdoor recreation camp like a mushroom. Thus, the opportunities to involve in outdoor recreation camp more variety. It is trusted that, by going to such camp, the participant can improve their execution in their day to day life. The assessment was finished by breaking down the adequacy criteria, the outer and inside components associated with the camp and the reasonableness of the exercises. From the questionnaire, information acquired were demographic characteristic and the participants’ level satisfaction towards outdoor recreation camp. The study uncovers that the components that impact the adequacy of outdoor recreation camp were outer factors, for example, modules led and the fundamental facilities in the camp. Then, there are changes in performance after participants have participated in program/ camp. The study concludes that the importance of outdoor recreation camp and the needs to evaluate the perception by identifying the strengths and weakness.